Full-employment labor supply in ireland - 1954-1970 - Slattery, D.G. (Economic & Social Studies, 1977)
In Ireland as in many other countries the attainment of full employment has become a central feature of government economic policy. In attempting to translate 'full employment' into quantitative terms it must be borne in mind that it is not normally the sole policy objective but must be seen in the context of other and possibly conflicting targets. With this in mind the author has recently suggested (Slattery 1976) that an unemployment rate of three per cent represented full employment of the labour force in Ireland during the period from 1954 to 1970 and that this would have been accompanied by annual percentage rates of increase of 12.6 in money wages and 4.6 in prices. Since a commitment to full employment necessitates a manpower policy designed to ensure compatability between the supply of and demand for labour, an essential element of which is an estimate of the numbers of workers likely to be involved, the purpose of the present paper is to translate full employment as defined above into terms of the numbers who would seek employment.
Keywords: Economics; Ireland